The impact of mental health training in nursing professionals in government schools of Koshi province of Nepal (Journal of Psychiatrists' Association of Nepal, 2024)
Background: Despite mental health being vital for coping with life’s challenges, achieving potential, and supporting community well-being, many Low and Middle-Income Countries (LMICs), including Nepal, still rely on institutional rather than community care. Studies have shown that adolescents, facing rapid changes and mental health challenges, benefit greatly from early intervention in schools, through the training of school health nurses in mental health.Objective: This study aims to evaluate the effectiveness of mental health training on knowledge, attitudes, and practices of school health nurses in Koshi Province, Nepal.Methods: A prospective, Descriptive Pre- and Post-test study amongst five batches of Government School Health Nurses was conducted over three weeks, using a non-probability, convenience sampling method. Data were collected using semi-structured forms and structuredquestionnaires. The available data analysed using descriptive statistics, paired t-tests for comparing pre and post-training results, and regression analysis.Results: The mean post-test scores (47.28) were significantly higher than pre-test scores (37.28), indicating effective training. The study population was normally distributed, and a moderate correlation (0.661) between pre- and post-test scores demonstrates consistent improvement. The difference between scores was statistically significant (p